SISTEM KETENAGAKERJAAN DALAM KONSTELASI HUKUM POSITIF DAN HUKUM ISLAM DI INDONESIA - Haris Djayadi (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2021)
This study aims to describe the meaning of the constellation of the labor system in the perspective of positive law and Islamic law. The labor system in Indonesia is regulated in Law no. 13 of 2003 concerning manpower. Meanwhile, labor in the study of Islamic law is explained in fiqh muamalah with the concept of ijarah or renting. The results of this study indicate that the relation of the labor system is found in the perspective of positive law and Islamic law. First, the labor system in which it describes